Генезис польсько-українських міждержавних економічних відносин - Гороть, А.; Прокопчук, К.; Horot, A.; Prokopchuk, K. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У цій статті здійснено спробу проаналізувати й охарактеризувати із погляду міжнародного права найваж- ливіші події із хроніки українсько-польських міждержавних економічних відносин у першій половині 90-х рр. ХХ ст. Також виділено основні етапи формування правової бази регулювання цих відносин на основі двостороннього співробітництва двох держав. The article analyzes the most important events of the chronicles of the Ukrainian-Polish bilateral economic relations in the first half of the 90s according to the international law. They are related, on the one hand, with the procedure of formation of the new regulatory framework on market principles, and on the other, with the development of the new forms and methods of cooperation that meet the modern standards of the international human rights. The main phases of the legal framework regulating as well as the main stages of the legal framework for the regulation of such relations on the basis of bilateral cooperation are given. The fledging periods of the legal contractual basis development in the Ukrainian-Polish bilateral economic relations at the initial stage of reforms are given in accordance with the nature of the agreements and the chronicle of major events. The legal model of bilateral cooperation is examined. It is destined to provide the changes within the economy of Ukraine and the Republic of Poland, to contribute to the use of market mechanisms and self-financing principles, to strengthen the companies’ relations as well as to transform them into the major subjects of cooperation, to bring partners’ interaction to the conditions of the world market in accordance with international legislation.
Genesis of the Polish-Ukrainian Interstate Economic Relations
Keywords: інтеграція; міждержавні відносини; українсько-польські відносини; integration; inter-state; the Ukrainian-Polish